Macro Fungi Diversity in The Sanggabuana Mountain Area, Karawang Regency, Tegalwaru District, West Java - Sumarouw, Achmad Alfio Dalish; Yafi, Ikhwal; Vansha, Fahriza Kemal; Noverita, Noverita (Journal of Tropical Biodiversity, 2024)
Sanggabuana Mountain is a mountain located within the territory of Karawang Regency. Administratively, the mountain is situated in Karawang Regency, Tegalwaru District, West Java. The height of the mountain is 1,291 meters above sea level (MDPL) and is the highest and only mountain in Karawang. The area has a high biodiversity, making it highly likely to find many macrofungi, especially macrofungi. This research was conducted to determine the diversity of macrofungi in the Sanggabuana Mountain area of Karawang Regency, Tegalwaru District, West Java. The type of research is exploratory and descriptive research, conducted on three observation routes; Route A (Cigentis), Route B (local plantations), and Route C (Kejayaan). The research results obtained a total of 23 species from 17 genera of macrofungi across the three observation routes, with the species diversity index in all three routes falling into the moderate diversity category. The highest encounter frequency of macrofungi on Route B was Ganoderma applanatum (23%), on Route A was Trametes sp (19%), and on Route C was Microporus xanthopus, Xylaria sp, and Inonotus sp (10%). The species dominance index on Route A falls into the high dominance category, while on Route B and C, it falls into the low dominance category.